Further notes on the genus Kuzicus Gorochov, 1993 (Orthoptera: Tettigoniidae: Meconematinae) with description of one new species from China - Li, Yun; Chen, Chun; Chang, Yanlin (Zootaxa, 2021)
In this paper, a new species is proposed, Kuzicus multispinus sp. nov., from China. Images of the new species and distribution map for the genus in China are provided. Type specimen is deposited in the Museum of Hebei University.